Linguistic Transition and Academic Literacy: A Study of Papuan Students’ Anecdotal Writing Performance in Jakarta During the 2024 Academic Year - Rajaguk-guk, Sastri Br; Murtadho, Fathiaty; Lustyantie, Ninuk (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to examine the dynamics of linguistic transition and academic literacy capabilities of Papuan students in writing anecdotal texts during the 2024 academic year in Jakarta. The research employs a qualitative approach with in-depth interview techniques involving six respondents from various regions in Papua (Deiyai, Paniai, Dogiyai, Nabire). Written data from anecdotal text production was analyzed based on Swales' (1990) genre analysis rubric and Ellis' (2008) linguistic error analysis, while interview data was analyzed using thematic coding through Atlas.ti software. The results show that most students still experience difficulties in understanding the structure of anecdotal text genres, mastering formal Indonesian language registers, and facing psychological barriers such as low self-confidence and negative stereotypes. However, two respondents (YM and RT) showed significant progress through active learning strategies such as translanguaging, writing workshops, and daily practice. Intervention recommendations proposed by respondents include academic bridging programs, peer mentoring systems, genre-based writing workshops, and culturally responsive teaching.